2000
DOI: 10.1016/s0894-1777(99)00069-2
|View full text |Cite
|
Sign up to set email alerts
|

Gas premixed combustion at high turbulence. Turbulent flame closure combustion model

Abstract: This paper is devoted to analyze the special class of turbulent premixed ames that we call intermediate steady propagation (ISP) ames. These ames are common to industrial premixed combustion chambers which operate at intensive turbulence when velocity pulsations are signi cantly higher than the amelet combustion velocity. They are characterized by a practically constant turbulent combustion velocity, controlled by turbulence, chemistry and molecular processes, and by an increasing ame width, controlled mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(134 citation statements)
references
References 17 publications
4
130
0
Order By: Relevance
“…In the developed combustion model the turbulent flame speed (u t ) is used, in order to track the computational cells in which the flame has propagated during the main stages of combustion after the ignition phase. The expression incorporated is the one proposed by Zimont/Lipatnikov and Chomiak [28,29], where only one calibration constant "A" needs to be tuned. This tuning process has been accomplished in the evaluation study of the combustion model [16], where the calibration constant has been found to be equal to 0.8.…”
Section: Laminar and Turbulent Burning Velocities (Ignition And Main mentioning
confidence: 99%
“…In the developed combustion model the turbulent flame speed (u t ) is used, in order to track the computational cells in which the flame has propagated during the main stages of combustion after the ignition phase. The expression incorporated is the one proposed by Zimont/Lipatnikov and Chomiak [28,29], where only one calibration constant "A" needs to be tuned. This tuning process has been accomplished in the evaluation study of the combustion model [16], where the calibration constant has been found to be equal to 0.8.…”
Section: Laminar and Turbulent Burning Velocities (Ignition And Main mentioning
confidence: 99%
“…To the the best of the present author's knowledge, the key equation of the extended Zimont model, that is, (19), has yet been substantiated by basic arguments [3,28,29,32,34,38] only in the case of a statistically planar one-dimensional premixed turbulent flame. Therefore, strictly speaking, the extended Zimont model yields the following joint closure:…”
Section: Discussionmentioning
confidence: 98%
“…The approximate equality of u t and |w e (z f )| may further be supported by invoking the so-called Zimont [32][33][34] Stevens et al [18], set 1 Stevens et al [18], set 2 Stevens et al [18], set 3 (c) Figure 2: Axial profiles of (a) the Reynolds-averaged combustion progress variable c(x), measured by Cho et al [15] and by Cheng and Shepherd [16], and the Favre-averaged combustion progress variable c(z), measured (b) by Li et al [17] and (c) by Stevens et al [18]. Symbols show experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…We employ the method of probability density function (PDF) to detect the mixture fraction and to model chemistry in the system (used for cases of premixed and non-premixed combustion). The Zimont model of the turbulent flame speed is used to enclose the turbulent quantities, typically used for cases of premixed combustion [28]. The non-premixed model of combustion solves transport equations for conserved scalar and mixture fractions.…”
Section: Combustion Modelmentioning
confidence: 99%